Coconut Oil Processing as a Learning Medium and Implementation of P5 at SMA 1 Wori: Pengolahan Minyak Kelapa Sebagai Media Pembelajaran dan Implementasi P5 di SMA 1 Wori - Mokosuli, Yermia; Mege, Revolson; Manampiring, Nonny; Matey, Meyer; Buyang, Dalle; Maidangkay, Vonny (Universitas Lancang Kuning, 2025)
North Sulawesi is identical with coconut plants, in addition to being a source of economy but also one of the leading commodities and inseparable from people's lives. However, until now coconut farmers still have difficulty getting quality and cheap consumption oil. Observing the problems of the community, State Senior High School 1 Wori raised it as material for the Pancasila Student Profile Strengthening Project (P5) Entrepreneurship Theme implementing coconut oil processing technology as well as a learning medium. However, the coconut oil processing carried out by students is still simple and of low quality. This activity aims to apply coconut oil processing technology as a learning medium and implementation of the Merdeka Belajar program at SMA 1 Wori to produce quality coconut oil. The method used is a combination of the Problem Based Learning method with the Life Skill Education approach to coconut processing entrepreneurship. Through this activity, students in addition to gaining knowledge and skills as well as direct experience of Life Skill Education to process coconut oil with technology and can produce quality coconut oil.